Clinical-morphologic principles of treatment chronic vulvitis - S. I. Kulinich (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The aim of the study was to prove a role of candidosis-bacterial and viral infections in formation of vulvitis and dysplasias, and to receive grounded results of etiotropic therapy. We surveyed and treated 209 patients with vulva diseases of contraction type, atrophy, ulcers, cracks and vesicles accompanied with itching, dispareunia and lack of effect from standard treatment. Patients were examined for infections and were divided into 3 main groups by character of infections found: genital candidiasis - in 77 patients, viral affections - 52, opportunistic flora - 19. The control group included 6 patients. Methods of verification of infections were PCR, inoculations, bacterioscopy. All patients underwent vulvoscopy, cytological scrapes from vulva and biopsy. According to data on duration of disease, expressiveness and dissemination of disease we revealed the severity of process. Results of the conducted research showed that infection of uterus cavity in modern conditions leads to difficult diagnosed chronic inflammatory process in endometrium and is one of the important reasons of formation of intrauterine pathology, which in its turn causes failures of assisted reproductive technology.